Usability Evaluation of ASN Management System Using UEQ Method - Suci, Suci Wulandari; Putri, Sukmawati Anggraeni (International Journal of Informatics and Computation, 2026)
This study evaluates the usability and user experience quality of the SIM-ASN system using the User Experience Questionnaire (UEQ) method. The evaluation measures six dimensions, namely attractiveness, perspicuity, efficiency, dependability, stimulation, and novelty, to identify the strengths and weaknesses of the system from the users’ perspective. This study utilizes quantitative analysis by calculating the mean score of each UEQ dimension and comparing the results with the UEQ benchmark dataset. We obtain mean scores of −0.14 for attractiveness, −0.05 for perspicuity, −0.03 for efficiency, −0.03 for dependability, −0.13 for stimulation, and −0.20 for novelty. Based on the UEQ interpretation scale, all dimensions fall within the neutral category, although several dimensions show slightly negative tendencies. Furthermore, the benchmark analysis categorizes all evaluated dimensions as “Bad,” indicating that the SIM-ASN system belongs to the lowest 25% compared with other products in the UEQ benchmark dataset. These findings indicate that the current system still requires improvements in interface design, usability efficiency, interaction quality, and feature innovation to enhance user satisfaction and engagement. Thus, this study demonstrates that the UEQ method can effectively identify usability problems and provide comprehensive insights for improving the quality of government-based information systems through a user-centered evaluation approach.